plz answer fast¤¤¤¤¤¤¤¤¤¤¤¤
Attachments:
![](https://hi-static.z-dn.net/files/dfb/956f40da7d5a9b9908f72db090529eab.jpg)
Answers
Answered by
1
Since cos (90-theta)= sin theta, sin(90-theta)=cos theta
Sec theta =cosec(90-theta)
Cosec theta= sec(90- theta)
Therefore on putting values we get
Sin theta. cos theta . sin theta .sin theta .cos theta/cosec theta. Cos theta .cos theta.sin theta/sec thet . - 2cos theta sin theta
Sec theta =cosec(90-theta)
Cosec theta= sec(90- theta)
Therefore on putting values we get
Sin theta. cos theta . sin theta .sin theta .cos theta/cosec theta. Cos theta .cos theta.sin theta/sec thet . - 2cos theta sin theta
adityakute1817:
Sorry by mistakenly solved it only halfly
Similar questions